High incidence of Pneumocystis jirovecii pneumonia in oncological patients: a 19-year study - Boldiš, V; Ondriska, F; Kováč, Ľ; Steinhübel, J; Bastlová, M (Epidemiologie, mikrobiologie, imunologie, 2023)
AIM: In the past, Pneumocystis jirovecii belonged to the Protozoa group, but is currently taxonomically included in the kingdom Fungi. P. jirovecii is an opportunistic pathogen, responsible for pneumocystis pneumonia with frequent complications of immunocompromised patients. Delayed initiation of appropriate therapy increases the risk of death in immunocompromised patient. The aim of this work was to determine and evaluate the reliability of methods of laboratory diagnosis of pneumocystosis used in routine laboratories as well as the occurrence of this disease in patients from Slovakia during 19 years. MATERIAL AND METHODS: The diagnosis is based on microscopic examination (Giemsa- and Gram-Weigert-staining) and detection of parasite DNA by classical or real-time PCR in bronchoalveolar lavage and sputum. RESULTS: Pneumocysts were detected in 190 persons (5.7%) from the whole group of patients. Cancer patients represented the riskiest group in terms of pneumocystosis, which was confirmed by the highest percentage (57.9%) of individuals infected with P. jirovecii. Compared with the PCR, 33.7% sensitivity and 100% specificity of microscopy was calculated by using a binary classification test. Molecular methods are more sensitive in the detection of P. jirovecii compared to microscopic evidence and currently represent a reliable detection system in the diagnosis of pneumocystosis. CONCLUSION: In view of the increasing number of immunocompromised persons, diagnostics of P. jirovecii in patients with pulmonary complications is essential. This was also confirmed in our study, where the number of examinations and detection of this opportunistic pathogen increased over the years.
Keywords: bronchoalveolární lavážní tekutina; Bronchoalveolar Lavage Fluid; microscopic evidence; Pneumocystis jirovecii; Reproducibility of Results; lidé; Sensitivity and Specificity; senzitivita a specificita; Immunocompromised Host; Pneumonia, Pneumocystis; Incidence; reprodukovatelnost výsledků; Pneumocystis carinii; incidence; pneumocystosis; imunokompromitovaný pacient; polymerase chain reaction (PCR); kvantitativní polymerázová řetězová reakce; pneumocystová pneumonie; Real-Time Polymerase Chain Reaction; Humans